Augmented Reality Book-Based “Nasretin Hoca” Folklore to Improve Reading Literacy for Elementary School Students - Elita Genc, Nurbaiti; Fatma Rabia, Supriyati (Universitas Negeri Surabaya, 2024)
Reading literacy in elementary schools is still less than optimal because the learning resources used are still not appropriate to students' learning needs. This study aims to examine the effectiveness of using Augmented Reality (AR) Books based on “Nasretin Hoca” folklore as an innovative method to improve students' reading literacy in Türkiye elementary schools. Integrating Augmented Reality Book technology into the “Nasretin Hoca” folklore during the learning process creates an interactive and in-depth reading experience for students. AR Book provides an engaging learning experience for students by visually presented 3D animation, sound, and video. This multimedia approach enhances students' reading literacy skills, specifically in the areas of comprehension, analysis, and evaluation. This study used a quasi-experimental quantitative research methodology, specifically a one-group pretest-posttest design model that involves conducting an experiment on a single group without a comparison group. The results showed that using AR Books based on “Nasretin Hoca” folklore significantly affects students' reading literacy skills in Türkiye elementary schools. The conclusion of the research is students experienced an increase in reading skills and were able to develop comprehension, analysis, and evaluation skills of reading content.